Quizartinib for the treatment of FLT3/ITD acute myeloid leukemia. (July 2014) - Levis, Mark
ABSTRACT: : FLT3/ITD acute myeloid leukemia is a poor prognosis disease driven by a constitutively activated receptor tyrosine kinase, making it an obvious target for drug development. The development of clinically effective FLT3 inhibitors has been slow, in part because many are multi-targeted inhibitors that are not selective or specific for FLT3. Quizartinib is the first small molecule FLT3 tyrosine kinase inhibitor expressly developed as a FLT3 inhibitor. It is potent, selective and has ideal pharmacokinetics in comparison to other compounds previously tested. This article summarizes its advantages and limitations, and details the insights into the biology of the disease that have been uncovered through the laboratory and clinical use of quizartinib.